PELATIHAN KOMERSIALISASI KRIYA BAMBU-BATIK INDONESIA JEPANG BAGI MITRA USAHA SAHABAT BAMBU YOGYAKARTA [TRAINING ON COMMERCIALIZATION OF INDONESIAN-JAPANESE BAMBOO-BATIK CRAFTS FOR BUSINESS PARTNER SAHABAT BAMBU YOGYAKARTA] - Sabrina O. Sihombing; Rudy Pramono; July Hidayat (Jurnal Sinergitas PKM & CSR, 2020)
Bamboo craft is one of the components of the creative economy that can support the country's economic growth. It's the kind of cooperation needed between the government, academics, business people and the craftsman community so that handicrafts are not only oriented towards the domestic market but can penetrate the export market to obtain higher economic value. Therefore, small industries with innovative products will advance the regional and national economy and eventualy can contribute to the country's foreign exchange when it successfully penetratrates the export market. The product chosen to be developed, namely bamboo-batik craft, already has IPR registration. This training aims to transfer systematic and standardized production system knowledge for bamboo crafts in Yogyakarta. The training was attended by 12 participants of bamboo craftsmen in Rimpak Village, Wonosobo Sapuran Regency. This training was facilitated by Mrs. Takayuki Shimizu from Japan. Participants were taught to craft bamboo combined with batik to become an export-value art object. Based on the results of the evaluation, the participants were impressed with the ability of the facilitator to craft bamboo into a work of art. The result of the training was that the participants' abilities improved in crafting bamboo into art objects. The next stage, the craft of bamboo-batik, will be developed for sale in the domestic handicraft market and penetrate the international market through the stages of the commercialization process as follows: 1) imagination, 2) incubation, 3) demonstration, 4) promotion, and 5) sustainability.Bahasa Indonesia Abstrak:  Abstrak Kerajinan bambu merupakan salah satu komponen ekonomi kreatif yang dapat menudukung pertumbuhan perekonomian negara. Hanya saja, diperlukan kerja sama antara pemerintah, akademisi, pelaku bisnis dan komunitas pengrajin agar hasil kerajinan tidak hanya berorientasi pada pasar domestik namun bisa menembus pasar ekspor untuk mrndapatkan nilai ekonomis yang tinggai. Oleh karena itu industri kecil dengan produk yang inovatif akan memajukan perekonomian regional, nasional dan akhirnya bisa ikut menyumbang devisa negara ketika berhasil menembus pasar ekspor. Produk yang dipilih untuk dikembangkan, yaitu kriya bambu-batik sudah memiliki pendaftaran HKI. Pelatihan ini bertujuan untuk melakukan transfer pengetahuan sistem produksi yang sistematis dan terstandarisasi bagi kerajinan bambu di Yogyakarta. Pelatihan diikuti oleh 12 peserta yang berasal dari pengrajin bambu Desa Rimpak, Kecamatan Sapuran Wonosobo. Pelatihan ini didampingi oleh Mrs. Takayuki Shimuzu dari Jepang. Peserta diajarkan mengolah bambu yang digabungkan dengan batik untuk menjadi benda seni yang bernilai ekspor. Berdasarkan hasil evaluasi, peserta terkesan dengan kemampuan fasilitator mengolah bambu menjadi sebuah karya seni. Hasil dari mengikuti pelatihan, kemampuan peserta meningkat dalam hal mengolah bambu mejadi benda seni. Tahap selanjutnya, kriya bambu batik akan dikembangkan untuk dijual di pasar kerajinan domestik dan menembus pasar internasional melalui tahapan proses komersialisasisebagaiberikut: (1) imajinasi,(2) inkubasi,(3) demonstrasi,(4) promosi, dan (5) keberlanjutan.